2020
DOI: 10.1002/ieam.4352
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of a Recommended Analytical and Classification Approach for Organic Fluorinated Compounds with an Emphasis on Per‐ and Polyfluoroalkyl Substances

Abstract: Organic fluorinated compounds have been detected in various environmental media and biota. Some of these compounds are regulated locally (e.g., perfluorononanoic acid maximum contaminant level in drinking water by the New Jersey Dept. of Environmental Protection), nationally (e.g., perfluorooctanoic acid maximum acceptable concentration in drinking water by Health Canada), or internationally (e.g., Stockholm Convention on Persistent Organic Pollutants). Globally, regulators and researchers seek to identify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…Currently, there is an increasing interest in determining inorganic and organic fluorine in many different types of samples ( 62 ). Thousands of organofluorine compounds have been developed, and they are becoming more heavily regulated ( 63 ), so new analytical methodologies are needed ( 24 , 64 ). There is also a need for determining inorganic fluorine, principally fluoride, in natural waters and in municipal drinking waters where fluoride is added for cavity prevention ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is an increasing interest in determining inorganic and organic fluorine in many different types of samples ( 62 ). Thousands of organofluorine compounds have been developed, and they are becoming more heavily regulated ( 63 ), so new analytical methodologies are needed ( 24 , 64 ). There is also a need for determining inorganic fluorine, principally fluoride, in natural waters and in municipal drinking waters where fluoride is added for cavity prevention ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Documentation of microbial degradation of fluorinated compounds typically requires monitoring parent compound disappearance and product appearance. Detecting defluorinated organic products often involves extractions followed by liquid or gas chromatography and mass spectrometry ( 23 , 24 ). With polyfluorinated compounds, these analytical methods can be difficult due to extraction losses, volatility during workup, and external contamination.…”
Section: Introductionmentioning
confidence: 99%
“…HFPO-DA was observed in one sample (location 10) with a high level (9.8 ng/L) as a result of the contamination by the fluorochemical plant in the Netherlands. 35 Although PFOS and PFOA have relatively recently been banned by an international restriction on use and production, 52,53 they are still present in drinking water (PFOS 0.05− 4.3 ng/L; PFOA 0.04−8.6 ng/L) (Table S3). Further curative measures such as remediation of these sources, use of alternative sources, or additional treatment would be needed to further diminish human exposure to these restricted compounds.…”
Section: Pfas Concentration In Raw and Producedmentioning
confidence: 99%
“…Additionally, the mean value of PFOA and PFOS obtained in this study was compared with the data of a few studies investigating the vulnerability of European river systems such as Kampen IJssel (Netherland), 28 Ebro River (Spain), 29 Thames River (United Kingdom), 30 and Rhine River (Germany) 31 in order to assess PFCs pollution levels, Table III *10 n.e. 24.09 ** Joint Danube Survey 3 27 8.50 7.20 Kampen IJssel (Netherland) n.d. 9.90 Ebro River (Spain) 29 125 27.0 Thames River (United Kingdom) 30 11.7 18.9 Rhine River (Germany) 31 3 It can be concluded that concentrations of PFOS in Kampen IJssel 28 and Rhine River 31 were of the same order, but a bit higher than the concentrations obtained in this study being 9.90 and 8.56 ng/L, respectively while concentrations in Ebro River 29 and Thames River 30 were 4.4 and 3.1 times higher than concentrations obtained in this study. In respect of PFOA concentrations in Rhiner River and Thames River were lower being 3.66 and 11.7 ng/L while concentrations in Ebro River were 10.3 times higher.…”
Section: Accepted Manuscriptmentioning
confidence: 99%